Do coping strategies moderate the relationship between escapism and negative gaming outcomes in World of Warcraft (MMORPG) players?. (September 2018) - Bowditch, Lorelle; Chapman, Janine; Naweed, Anjum
Abstract: A link between escapist motivations for playing Massively Multiplayer Online Role-Playing Games (MMORPGs) and negative outcomes associated with play has been previously established. However, not all escapists experience the same level of negative gaming outcomes, and the underlying mechanisms have yet to be explored. The purpose of this study was to determine if individual differences in engaged and disengaged coping styles could explain differences in outcomes. Cross-sectional survey data from adult players of World of Warcraft (WoW) were collected ( N = 217), using measures of negative gaming outcomes, escapism, and individual coping style. Primary analysis revealed that disengaged coping strategies were positively correlated with both escapist motivations and negative outcomes, and the engaged coping strategies of Problem Solving and Social Support were negatively correlated with negative gaming outcomes. The main analyses revealed that the relationship between escapist motivations for play and negative gaming outcomes was moderated by problem-focused coping strategies. This study offers novel insight into video game research, demonstrating that individual coping styles play a role in moderating the relationship between gaming motivation and the negative outcomes associated with video gaming. Highlights: Assessed the effect of coping on the relationship between escapism and outcomes. Escapism does not necessarily lead to adverse effects. Disengaged coping is positively correlated with negative outcomes. Engaged problem-focused coping protects against negative gaming outcomes. Coping style moderates the relationship between escapism and negative outcomes.